Optical film and polarizing plate
Patent Information
- Application Number
- CN202280009617.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-01-31
- Filing Date
- 2022-02-15
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-02-15
AI Technical Summary
[0022] It is possible to provide an optical film based on (meth)acrylic resin that can improve the adhesion between the film and the polarizer when placed in a high temperature and high humidity environment.
Smart Images

Figure CN116723938B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to optical films and polarizing plates. Background Technology
[0002] Polarizing plates, widely used in image display devices such as liquid crystal displays and organic EL displays, typically have a structure in which a thermoplastic resin film is laminated as a protective film on one or both sides of the polarizing plate. Japanese Patent Application Publication No. 2008-102274 (Patent Document 1) discloses that an acrylic resin film can be used as a protective film.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2008-102274 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] For polarizing plates using (meth)acrylic resin film as a protective film, there is room for improvement in the adhesion between the polarizing plate and the (meth)acrylic resin film when placed in a high temperature and high humidity environment.
[0008] The object of the present invention is to provide an optical film based on (meth)acrylic resin that can improve the above-mentioned adhesion.
[0009] Methods for solving problems
[0010] The present invention provides the optical film and polarizing plate shown below.
[0011] [1] An optical film comprising a resin layer comprising (meth)acrylic resin (A), (meth)acrylic resin (B), and an elastomer component (C),
[0012] The syn-isotactic normality of the above-mentioned (meth)acrylic resin (A) is higher than that of the above-mentioned (meth)acrylic resin (B).
[0013] When the content of the (meth)acrylic resin (A) in the above resin layer is set as A (parts by mass) and the content of the above elastomer component (C) is set as C (parts by mass), the above resin layer satisfies the following formula [1]:
[0014] A / (A+C)<0.6 Formula[1]
[0015] [2] According to the optical film described in [1], when the content of the above-mentioned (meth)acrylic resin (B) in the above-mentioned resin layer is set to B (parts by mass), the following formula [2] is further satisfied:
[0016] 0.05≤A / (A+B)≤0.4 Equation [2]
[0017] [3] The optical film described in [1] or [2], wherein the above-mentioned elastomer component (C) is rubber particles.
[0018] [4] The optical film according to any one of [1] to [3] further comprises a surface treatment layer laminated on the above-mentioned resin layer.
[0019] [5] The optical film described in any one of [1] to [4] is a protective film for polarizing film.
[0020] [6] A polarizing plate comprising, in sequence, a polarizing film, an adhesive layer and an optical film described in any one of [1] to [5].
[0021] Invention Effects
[0022] It is possible to provide an optical film based on (meth)acrylic resin that can improve the adhesion between the film and the polarizer when placed in a high temperature and high humidity environment. Attached Figure Description
[0023] Figure 1 This is a schematic cross-sectional view illustrating an example of the layered structure of the polarizing plate of the present invention.
[0024] Figure 2 This is a schematic cross-sectional view showing another example of the layered structure of the polarizing plate of the present invention. Detailed Implementation
[0025] <Optical film>
[0026] The optical film of the present invention (hereinafter also referred to as "optical film") is a film having a resin layer comprising (meth)acrylic resin (A), (meth)acrylic resin (B) and an elastomer component (C), and can be suitably used as a protective film for polarizers.
[0027] Hereinafter, (meth)acrylic resin (A), (meth)acrylic resin (B), and elastomer component (C) will be referred to as "component (A)," "component (B)," and "component (C)," respectively.
[0028] Component (A) and component (B) have different degrees of homonormality, specifically, component (A) has a higher degree of homonormality than component (B).
[0029] In this specification, "(meth)acrylic acid" means selected from at least one of acrylic acid and methacrylic acid. The same applies to the terms "(meth)acryloyl" and "(meth)acrylate".
[0030] When the content of component (A) in the resin layer is set as A (parts by mass) and the content of component (C) is set as C (parts by mass), the resin layer satisfies the following formula [1]:
[0031] A / (A+C)<0.6 Formula[1]
[0032] When the optical film of the present invention is bonded to a polarizer using an adhesive, it exhibits good adhesion to the polarizer, thereby ensuring good durability of the polarizer. In particular, the optical film of the present invention maintains good adhesion to the polarizer even when exposed to high temperature and high humidity environments, thus ensuring good durability of the polarizer under such conditions.
[0033] [1] Composition of optical films
[0034] The optical film can be a single-layer film, that is, it can contain the aforementioned resin layer. Alternatively, the optical film can also contain other layers besides the aforementioned resin layer, such as a surface treatment layer (coating layer).
[0035] [2] Resin layer
[0036] The resin layer comprises components (A), (B), and (C). The thickness of the resin layer is typically 5 μm or more and 200 μm or less, preferably 10 μm or more and 120 μm or less, more preferably 10 μm or more and 85 μm or less, and even more preferably 15 μm or more and 65 μm or less. The thickness of the resin layer can also be 60 μm or less, or 50 μm or less. Reducing the thickness of the resin layer facilitates the thinning of the polarizing plate, and consequently, the thinning of image display devices, etc., that utilize this polarizing plate.
[0037] The resin layer may contain other resin components besides component (A) and component (B).
[0038] From the viewpoint of heat resistance and toughness of the optical film, it is preferable that the total content of component (A) and component (B) in the resin components (excluding component (C)) contained in the resin layer is high, preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more.
[0039] Component (A) is preferably a polymer with methacrylate as the main monomer (containing more than 50% by mass). Component (A) can be a homopolymer of methacrylate or a copolymer of methacrylate and other copolymers.
[0040] The content of structural units derived from methacrylate in component (A) is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 98% by mass or more, even more preferably 99% by mass or more, and particularly preferably 100% by mass.
[0041] In one preferred embodiment, component (A) is a homopolymer of methacrylate. In another preferred embodiment, component (A) is a homopolymer of methyl methacrylate.
[0042] Examples of the aforementioned methacrylates include methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate or tert-butyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, benzyl methacrylate, 2-ethylhexyl methacrylate, 2-hydroxyethyl methacrylate, etc. Component (A) may contain one or more structural units derived from methacrylates.
[0043] The methacrylate preferably includes methyl methacrylate, and more preferably methyl methacrylate.
[0044] Other copolymer components mentioned above can be cited as examples:
[0045] Acrylates such as ethyl acrylate, n-butyl acrylate, isobutyl acrylate or tert-butyl acrylate, cyclohexyl acrylate, phenyl acrylate, benzyl acrylate, 2-ethylhexyl acrylate, and 2-hydroxyethyl acrylate;
[0046] Hydroxyalkyl acrylates such as methyl 2-(hydroxymethyl)acrylate, methyl 2-(1-hydroxyethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, n-butyl 2-(hydroxymethyl)acrylate, isobutyl acrylate or tert-butyl acrylate;
[0047] Unsaturated acids such as methacrylic acid and acrylic acid;
[0048] Halogenated styrene derivatives such as chlorostyrene and bromostyrene;
[0049] Vinyltoluene, α-methylstyrene, and other substituted styrene derivatives;
[0050] Unsaturated nitriles such as acrylonitrile and methacrylonitrile;
[0051] Unsaturated anhydrides such as maleic anhydride and citrate anhydride;
[0052] Unsaturated imides such as phenylmaleimide and cyclohexylmaleimide; and monofunctional monomers.
[0053] The other monofunctional monomers mentioned above can be used alone or in combination with two or more.
[0054] Multifunctional monomers can also be used as other copolymer components mentioned above.
[0055] Examples of multifunctional monomers include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, nonaethylene glycol di(meth)acrylate, tetradecaethylene glycol di(meth)acrylate, and tetradecaethylene glycol di(meth)acrylate, which are compounds obtained by esterifying the two terminal hydroxyl groups of ethylene glycol or its oligomers with (meth)acrylate.
[0056] A compound obtained by esterifying the two terminal hydroxyl groups of propylene glycol or its oligomers with (meth)acrylic acid;
[0057] Neopentyl glycol di(meth)acrylate, hexanediol di(meth)acrylate, butanediol di(meth)acrylate, etc. are compounds obtained by esterifying the hydroxyl groups of diols with (meth)acrylic acid.
[0058] Compounds obtained by esterification of the terminal hydroxyl groups of bisphenol A, bisphenol A alkylene oxide adducts, or their halogenated derivatives with (meth)acrylic acid.
[0059] Compounds obtained by esterification of polyols such as trimethylolpropane and pentaerythritol with (meth)acrylic acid, and compounds obtained by ring-opening addition of glycidyl methacrylate to the terminal hydroxyl groups of these compounds.
[0060] Compounds obtained by ring-opening addition of succinic acid, adipic acid, terephthalic acid, phthalic acid, their halogenated derivatives, or their alkyl oxide adducts to the epoxy group of glycidyl (meth)acrylate.
[0061] Aryl methacrylates; aromatic divinyl compounds such as divinylbenzene; etc.
[0062] The weight-average molecular weight Mw of component (A) is, for example, 40,000 or more and 150,000 or less. From the viewpoint of the heat resistance of the optical film, the adhesion to the polarizer and the formability of the film, it is preferably 40,000 or more and 120,000 or less, and more preferably 50,000 or more and 100,000 or less.
[0063] The molecular weight distribution (weight-average molecular weight Mw / number-average molecular weight Mn) of component (A) is, for example, 1.01 or more and 1.8 or less. From the viewpoint of the heat resistance of the optical film and its adhesion to the polarizer, it is preferably 1.03 or more and 1.5 or less, and more preferably 1.05 or more and 1.3 or less.
[0064] Mw and Mn can be controlled by adjusting the type and / or amount of polymerization initiator used in the preparation of component (A). Mw and Mn can be determined using gel permeation chromatography (GPC) (converted to standard polystyrene).
[0065] From the viewpoint of improving the toughness of the optical film, the glass transition temperature (Tg) of component (A) is preferably 110°C or higher and 160°C or lower, more preferably 120°C or higher and 150°C or lower, and even more preferably 125°C or higher and 140°C or lower. Tg can be controlled by adjusting the molecular weight, isotropic normality, etc.
[0066] The isoregulation (rr) of the ternary group of component (A) is, for example, 55% or more, and preferably 60% or more, more preferably 65% or more, and even more preferably 70% or more, from the viewpoint of improving the toughness and heat resistance of the optical film. The isoregulation (rr) of the ternary group of component (A) is generally 90% or less, and may also be 85% or less.
[0067] The syn-homogeneous normality (rr) expressed by a ternary unit group is the proportion of two chains (diad) in a chain of three consecutive structural units (triad) that are racemic (expressed as rr). The syn-homogeneous normality (rr) (%) expressed by a ternary unit group is calculated as follows, i.e., in CDCL3, measured at 30°C. 1 The H-NMR spectrum was used to measure the area (X) of the region from 0.6 to 0.95 ppm and the area (Y) of the region from 0.6 to 1.35 ppm when the internal standard TMS was set to 0 ppm. The result was calculated using (X / Y) × 100.
[0068] The syndiotacticity (rr) represented by the ternary unit group is within the above range. Component (A) can be prepared, for example, according to the method described in International Publication No. 2016 / 080124. By lowering the polymerization temperature or extending the polymerization time, the proportion of the syndiotacticity (rr) represented by the ternary unit group can be increased.
[0069] Component (B) may be, for example, a polymer with methacrylate as the main monomer (containing more than 50% by mass), preferably a copolymer of methacrylate and other copolymers. In a preferred embodiment, component (B) is a copolymer comprising structural units derived from methyl methacrylate. In another preferred embodiment, component (B) is a copolymer comprising structural units derived from methyl methacrylate and structural units derived from methyl acrylate.
[0070] Other copolymer components besides methyl acrylate include, for example, compounds exemplified for component (A) as methacrylate and other copolymer components.
[0071] The weight-average molecular weight (Mw) of component (B) is, for example, 40,000 or more and 150,000 or less. From the viewpoint of the heat resistance of the optical film, the adhesion to the polarizer, and the formability of the film, it is preferably 40,000 or more and 130,000 or less, and more preferably 50,000 or more and 120,000 or less.
[0072] The molecular weight distribution (weight-average molecular weight Mw / number-average molecular weight Mn) of component (B) is, for example, 1.01 or more and 2.5 or less. From the viewpoint of the heat resistance of the optical film and its adhesion to the polarizer, it is preferably 1.03 or more and 2.4 or less, and more preferably 1.05 or more and 2.3 or less.
[0073] Mw and Mn can be controlled by adjusting the type and / or amount of polymerization initiator used in the preparation of component (B). Mw and Mn can be determined using gel permeation chromatography (GPC) (converted to standard polystyrene).
[0074] The glass transition temperature (Tg) of component (B) is preferably 80°C or higher and 140°C or lower, more preferably 90°C or higher and 130°C or lower, and even more preferably 90°C or higher and 125°C or lower. Tg can be controlled by adjusting the molecular weight, isotropic normality, etc.
[0075] The syntagmatic normality (rr) of the ternary group of component (B) is lower than that of component (A). The syntagmatic normality (rr) of the ternary group of component (B) is, for example, 25% or more and 60% or less, preferably 30% or more and 55% or less, and more preferably 40% or more and less than 55%.
[0076] Component (B) can be prepared, for example, by reference to the methods described in Japanese Patent Application Publication Nos. 2009-145397 and 2021-155698. Component (B) can also be a compound prepared by free radical polymerization.
[0077] The resin layer contains component (C). The presence of component (C) is beneficial for improving the toughness of the optical film and its adhesion to the polarizer. Rubber particles can be cited as an example of component (C).
[0078] Rubber particles are rubber elastomer particles containing layers exhibiting rubber elasticity. Rubber particles can be particles containing only layers exhibiting rubber elasticity, or they can be multilayered particles having other layers in addition to layers exhibiting rubber elasticity. Examples of rubber elastomers include olefin-based elastic polymers, diene-based elastic polymers, styrene-diene elastic copolymers, and acrylic elastic polymers. Among these, acrylic elastic polymers are preferred from the viewpoint of the lightfastness and transparency of the optical film.
[0079] Acrylic elastic polymers can be polymers with alkyl acrylates as the main component, that is, polymers containing more than 50% by mass of structural units derived from alkyl acrylates based on the total monomer content. Acrylic elastic polymers can be homopolymers of alkyl acrylates, or copolymers containing more than 50% by mass of structural units derived from alkyl acrylates and less than 50% by mass of structural units derived from other polymerizable monomers.
[0080] As a constituent of acrylic elastic polymers, alkyl acrylates with 4 to 8 carbon atoms are typically used.
[0081] Other polymerizable monomers mentioned above include, for example, alkyl methacrylates such as methyl methacrylate and ethyl methacrylate; styrene monomers such as styrene and alkylstyrene; monofunctional monomers such as acrylonitrile and methacrylonitrile; unsaturated carboxylic acid esters such as allyl methacrylate and methallyl methacrylate; dienyl esters of dicarboxylic acids such as diallyl maleate; and polyfunctional monomers such as diol unsaturated carboxylic acid diesters such as alkylene glycol di(meth)acrylate.
[0082] The rubber particles containing acrylic elastic polymers are preferably multilayered particles having layers of acrylic elastic polymers. Specifically, examples include two-layered particles having a rigid polymer layer primarily composed of alkyl methacrylates on the outer side of the acrylic elastic polymer layers, and three-layered particles having a rigid polymer layer primarily composed of alkyl methacrylates on the inner side of the acrylic elastic polymer layers. Alkyl methacrylates are preferably methyl methacrylate.
[0083] Preferably, the average particle size of the rubber particles, up to the rubber elastomer layer (a layer of acrylic elastic polymer) contained therein, is in the range of 10 nm or more and 350 nm or less. This average particle size range is beneficial for improving the toughness of the optical film and its adhesion to the polarizer. More preferably, the average particle size is 30 nm or more, even more preferably 50 nm or more, even more preferably 320 nm or less, and even more preferably 300 nm or less.
[0084] The average particle size of the rubber particles up to the rubber elastomer layer (the layer of the acrylic elastomer) can be determined as follows. Specifically, if such rubber particles are mixed with a (meth)acrylic resin and film-formed, and their cross-section is stained with an aqueous solution of ruthenium oxide, only the rubber elastomer layer is stained and observed to be approximately spherical; the parent (meth)acrylic resin layer is not stained. Therefore, thin sections are prepared from the stained film cross-section using an ultramicrotome or similar instrument, and observed using an electron microscope. Subsequently, 100 stained rubber particles are randomly selected, and their individual particle diameters (diameter up to the rubber elastomer layer) are calculated. The number average of these diameters is then taken as the average particle size. Since this method is used for measurement, the obtained average particle size is the number-average particle size.
[0085] In the case of rubber particles whose outermost layer is a rigid polymer mainly composed of methyl methacrylate and which contains a layer of rubber elastomer (an acrylic elastomer layer), if they are mixed with a parent (meth)acrylic resin, the outermost layer of the rubber particle mixes with the parent (meth)acrylic resin. Therefore, if the cross-section is stained with ruthenium oxide and observed with an electron microscope, the rubber particle is observed as a particle with the outermost layer removed. Specifically, in the case of rubber particles with a two-layer structure of an acrylic elastomer inner layer and a rigid polymer mainly composed of methyl methacrylate outer layer, the acrylic elastomer portion of the inner layer is stained and observed as a single-layer structure particle. Furthermore, in the case of rubber particles with a three-layer structure of a rigid polymer mainly composed of methyl methacrylate inner layer, an acrylic elastomer middle layer, and a rigid polymer mainly composed of methyl methacrylate outer layer, the innermost particle's central portion is not stained, but only the acrylic elastomer portion of the middle layer is stained, resulting in a two-layer structure particle.
[0086] The resin layer satisfies the above formula [1]. Therefore, when the optical film is bonded to the polarizer using an adhesive, the adhesion to the polarizer becomes good, especially when exposed to a high temperature and high humidity environment, the adhesion to the polarizer becomes good. A / (A+C) can also be 0.55 or less, 0.50 or less, 0.45 or less, or 0.40 or less.
[0087] From the perspective of the above-mentioned tightness, A / (A+C) is preferably 0.1 or more, and more preferably 0.2 or more.
[0088] When setting the content of component (B) as B (parts by mass), it is preferable that B is greater than A.
[0089] The resin layer preferably further satisfies the following formula [2]:
[0090] 0.05≤A / (A+B)≤0.4 Equation [2]
[0091] Satisfying equation [2] is beneficial to improving the toughness of the optical film and its tightness with the polarizer.
[0092] A / (A+B) is preferably 0.10 or more and 0.35 or less, more preferably 0.15 or more and 0.30 or less.
[0093] From the viewpoint of the toughness of the optical film and its adhesion to the polarizer, the content of component (A) in the resin layer is preferably 1% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 40% by mass or less, even more preferably 10% by mass or more and 35% by mass or less, and even more preferably 15% by mass or more and 30% by mass or less.
[0094] From the viewpoint of the toughness of the optical film and its adhesion to the polarizer, the content of component (B) in the resin layer is preferably 10% by mass or more and 95% by mass or less, more preferably 20% by mass or more and 90% by mass or less, even more preferably 30% by mass or more and 80% by mass or less, and even more preferably 40% by mass or more and 70% by mass or less.
[0095] From the viewpoint of the toughness of the optical film and its adhesion to the polarizer, the content of component (C) in the resin layer is preferably 1% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 40% by mass or less, even more preferably 10% by mass or more and 35% by mass or less, and even more preferably 15% by mass or more and 35% by mass or less.
[0096] The resin layer may contain other components besides those mentioned above, as needed. Examples of such other components include lubricants, anti-blocking agents, heat stabilizers, antioxidants, UV absorbers, antistatic agents, impact modifiers, surfactants, and release agents.
[0097] When the tensile modulus of elasticity in the MD direction at 23°C is set to E23(MD) and the tensile modulus of elasticity in the TD direction at 23°C is set to E23(TD), the resin layer preferably satisfies the following formula [3]:
[0098] 0.5≤E23(TD) / E23(MD)≤1.5 Equation [3]
[0099] In formula [3], E23(TD) / E23(MD) can be 0.6 or higher and 1.4 or lower, 0.7 or higher and 1.3 or lower, 0.8 or higher and 1.3 or lower, 0.9 or higher and 1.3 or lower, 0.9 or higher and 1.2 or lower, or 0.9 or higher and 1.1 or lower. The units of E23(MD) and E23(TD) are MPa.
[0100] In order to satisfy the above formula [3], the resin layer is preferably unstretched.
[0101] When the tensile modulus of elasticity in the MD direction at 80°C is set to E80(MD) and the tensile modulus of elasticity in the TD direction at 80°C is set to E80(TD), the resin layer preferably satisfies the following formula [4]:
[0102] 0.5≤E80(TD) / E80(MD)≤1.5 Equation [4]
[0103] In formula [4], E80(TD) / E80(MD) can be 0.6 or higher and 1.4 or lower, 0.7 or higher and 1.3 or lower, 0.8 or higher and 1.3 or lower, 0.9 or higher and 1.3 or lower, 0.9 or higher and 1.2 or lower, or 0.9 or higher and 1.1 or lower. The units of E80(MD) and E80(TD) are MPa.
[0104] The optimal absorbed energy (Charpy impact strength) of the resin layer, as determined by Charpy impact testing, is 140 kJ / m. 2 The above, more preferably 160 kJ / m 2 The above is further optimized to 170 kJ / m 2 The above is further optimized to 180 kJ / m 2 The above is particularly preferred, with 200 kJ / m 2 That's all. Charpy impact strength is typically 350 kJ / m. 2 The following can also be 300 kJ / m 2 The Charpy impact test was conducted at a temperature of 23°C and a relative humidity of 50% RH.
[0105] Setting the Charpy impact strength to the above range is beneficial to improving the adhesion between the polarizer and the optical film, especially when the polarizer is placed in a high temperature and high humidity environment.
[0106] The tensile modulus of elasticity and Charpy impact strength of the resin layer can be determined using the method described in the [Example] section below.
[0107] [3] Surface treatment layer
[0108] Examples of surface treatment layers include hard coatings, anti-glare layers, anti-reflective layers, light diffusion layers, antistatic layers, anti-fouling layers, and conductive layers, with hard coatings being preferred. It should be noted that the surface treatment layer can be a single layer with multiple functions, or it can be a layer with, for example, hard coating and anti-glare properties. The surface treatment layer (coating layer) is laminated onto the aforementioned resin layer, typically directly laminated onto the resin layer. In a polarizing plate formed by bonding an optical film to a polarizer, the surface of the resin layer to which the surface treatment layer is laminated is typically the surface opposite to the polarizer side.
[0109] As a surface treatment layer, an example is a cured layer of a curable resin composition containing an active energy ray curable compound. The active energy ray curable compound is a compound that polymerizes and cures upon irradiation by active energy rays such as ultraviolet light or electron beams.
[0110] Examples of active energy ray curable compounds include monofunctional, difunctional, or trifunctional (meth)acrylate compounds. One or more active energy ray curable compounds may be used.
[0111] Examples of monofunctional (meth)acrylate compounds include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, glycidyl (meth)acrylate, acryloylmorpholine, N-vinylpyrrolidone, tetrahydrofurfuryl acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and isobornyl (meth)acrylate. Isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, benzyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, meth phosphate, ethylene oxide modified meth phosphate, phenoxy (meth)acrylate, ethylene oxide modified phenoxy (meth)acrylate, propylene oxide modified (meth)acrylate Phthalate acrylate, nonylphenol (meth) acrylate, ethylene oxide modified nonylphenol (meth) acrylate, propylene oxide modified nonylphenol (meth) acrylate, methoxydiethylene glycol (meth) acrylate, methoxypolyethylene glycol (meth) acrylate, methoxypropylene glycol (meth) acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl phthalate, 2-hydroxy-3-phenoxypropyl phthalate (Meth)acryloyloxypropyl ester, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl tetrahydrophthalic acid, dimethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate, adamantane derivative mono(meth)acrylates (e.g., adamantyl acrylate having a monovalent mono(meth)acrylate derived from adamantanediol), etc.
[0112] Examples of difunctional (meth)acrylate compounds include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, ethoxylated hexanediol di(meth)acrylate, propoxylated hexanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol... Di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, isocyanuric acid di(meth)acrylate, hydroxypentanoic acid neopentyl glycol di(meth)acrylate, adamantyl di(meth)acrylate, isobornyl di(meth)acrylate, dicyclopentane di(meth)acrylate, tricyclodecane di(meth)acrylate, and other di(meth)acrylates.
[0113] Examples of trimethylolpropane trimethacrylate compounds with three or more functionalities include trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane trimethacrylate, propoxylated trimethylolpropane trimethacrylate, tris(2-hydroxyethyl)isocyanurate trimethacrylate, glycerol trimethacrylate, pentaerythritol trimethacrylate, dipentaerythritol trimethacrylate, bis(trimethylolpropane)trimethacrylate, pentaerythritol tetramethacrylate, bis(trimethylolpropane)tetramethacrylate, and di... Pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, bis(trimethylolpropane)tetra(meth)acrylate, bis(trimethylolpropane)penta(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, bis(trimethylolpropane) hexa(meth)acrylate, tripentaerythritol octa(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, etc. In addition, polyfunctional (meth)acrylate compounds in which a portion of these (meth)acrylates is replaced by alkyl groups or ε-caprolactones can also be cited.
[0114] Other examples of active energy ray-curable compounds include oligomers or polymers such as urethane (meth)acrylates, isocyanurate (meth)acrylates, polyester-urethane (meth)acrylates, and epoxy (meth)acrylates.
[0115] Examples of urethane (meth)acrylates include pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, and dipentaerythritol pentaacrylate isophorone diisocyanate urethane prepolymer.
[0116] The curable resin composition may further comprise a thermoplastic resin. Examples of thermoplastic resins include styrene-based resins, (meth)acrylate-based resins, vinyl acetate-based resins, vinyl ether-based resins, halogen-containing resins, alicyclic olefin-based resins, polycarbonate-based resins, polyester-based resins, polyamide-based resins, cellulose derivatives, silicone-based resins, and rubbers or elastomers.
[0117] The curable resin composition may further comprise a thermosetting resin. Examples of thermosetting resins include phenolic resins, urea resins, diallyl phthalate resins, melamine resins, guanidine resins, unsaturated polyester resins, polyurethane resins, epoxy resins, amino alkyd resins, melamine-urea cocondensation resins, silicone resins, and polysiloxane resins.
[0118] The curable resin composition may contain one or more photoradical polymerization initiators. Examples of photoradical polymerization initiators include acetophenones, benzophenones, mihizolide benzoates, α-pentoxime esters, thioxanones, phenylacetones, benzoyl esters, benzoin esters, and phosphine oxides. The curable resin composition may further contain one or more photosensitizers. Examples of photosensitizers include n-butylamine, triethylamine, and polyn-butylphosphine.
[0119] The curable resin composition may further comprise organic and inorganic microparticles. Examples of organic microparticles include those selected from acrylic resins, polystyrene resins, styrene-acrylic copolymers, polyethylene resins, epoxy resins, silicone resins, polyvinylidene fluoride resins, and polyvinyl fluoride resins. Examples of inorganic microparticles include silica (SiO2) microparticles, alumina microparticles, titanium dioxide microparticles, tin oxide microparticles, antimony-doped tin oxide (ATO) microparticles, zinc oxide microparticles, etc., with silica microparticles being preferred. Amorphous silica particles are preferred. Examples of amorphous silica microparticles include pyrolytic silica microparticles and colloidal silica. Silica microparticles may be surface-modified. The average primary particle size of the silica microparticles is preferably 200 nm or less, more preferably 100 nm or less. The lower limit of the average primary particle size of the silica microparticles is not particularly limited, for example, it may be 1 nm or more.
[0120] The curable resin composition may contain one or more solvents. Examples of solvents include alcohols (such as methanol, ethanol, propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, benzyl alcohol, PGME, ethylene glycol), ketones (acetone, methyl ethyl ketone (MEK), cyclohexanone, methyl isobutyl ketone, diacetone alcohol, cycloheptanone, diethyl ketone, etc.), ethers (1,4-dioxane, dioxolane, diisopropyl ether dioxane, tetrahydrofuran, etc.), aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated carbons (dichloromethane, dichloroethane, etc.), esters (methyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl lactate, etc.), cellosols (methyl cellosol, ethyl cellosol, butyl cellosol, etc.), cellosol acetates, sulfoxides (dimethyl sulfoxide, etc.), and amides (dimethylformamide, dimethylacetamide, etc.).
[0121] The solid content (the total amount of the active energy ray curable compound, thermoplastic resin and thermosetting resin) of the curable resin composition is, for example, 5% by mass or more and 70% by mass or less, preferably 25% by mass or more and 60% by mass or less.
[0122] The content of the photoradical polymerization initiator in the curable resin composition is preferably 0.5 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the active energy ray curable compound.
[0123] The thickness of the surface treatment layer, such as the hard coating, is, for example, 0.1 μm or more and 50 μm or less, preferably 0.5 μm or more and 30 μm or less, more preferably 1 μm or more and 20 μm or less, and even more preferably 1 μm or more and 10 μm or less.
[0124] <Polarizing plate>
[0125] In this specification, "polarizing plate" refers to an optical laminate comprising a polarizer and a thermoplastic resin film laminated on one or both sides thereof. In the polarizing plate, the polarizer and the aforementioned thermoplastic resin film are laminated via an adhesive layer. The adhesive layer is a layer formed of an adhesive composition, such as a cured layer of the adhesive composition.
[0126] The polarizing plate may also contain films or layers other than polarizing sheets and the aforementioned thermoplastic resin films.
[0127] The polarizing plate of the present invention sequentially comprises a polarizer, an adhesive layer, and the optical film of the present invention described above. Typically, the polarizer is in contact with the adhesive layer, and the adhesive layer is in contact with the optical film. Because the polarizing plate of the present invention uses the optical film of the present invention as a protective film for the polarizer, the adhesion between the polarizer and the optical film is excellent, thereby improving the durability of the polarizing plate. In particular, the adhesion between the polarizer and the optical film remains excellent even when exposed to high temperature and high humidity environments, thus improving durability under such conditions.
[0128] The polarizing plate of the present invention can be suitably used in image display devices such as liquid crystal display devices and organic EL devices.
[0129] [1] Structure of polarizing plate
[0130] An example of the layer structure of the polarizing plate of the present invention is shown in Figure 1 and Figure 2 middle.
[0131] like Figure 1 As shown, the polarizing plate of the present invention may sequentially include a polarizing sheet 30, a first adhesive layer 15, and a first thermoplastic resin film 10 as the optical film of the present invention described above. That is, it may include a polarizing sheet 30 and a first thermoplastic resin film 10 laminated and bonded to one side of the polarizing sheet via the first adhesive layer 15.
[0132] A primer layer can be sandwiched between the first adhesive layer 15 and the first thermoplastic resin film 10, or the first adhesive layer 15 can be in direct contact with the first thermoplastic resin film 10. Preferably, the polarizer 30 is in direct contact with the first adhesive layer 15.
[0133] In addition, such as Figure 2 As shown, the polarizing plate of the present invention may include a polarizing film 30, a first thermoplastic resin film 10 which is an optical film of the present invention and is laminated to one side thereon via a first adhesive layer 15, and a second thermoplastic resin film 20 which is laminated to the other side of the polarizing film 30 via a second adhesive layer 25.
[0134] Preferably, the first adhesive layer 15 is in direct contact with the first thermoplastic resin film 10. Preferably, the polarizer 30 is in direct contact with the first adhesive layer 15. Preferably, the second adhesive layer 25 is in direct contact with the second thermoplastic resin film 20. Preferably, the polarizer 30 is in direct contact with the second adhesive layer 25.
[0135] The polarizer of the present invention is preferably mounted in an image display device with the first thermoplastic resin film 10 side as the observation side. That is, the optical film of the present invention is preferably a protective film laminated on the observation side of the polarizer 30.
[0136] Not limited to Figure 1 and Figure 2 For example, the polarizing plate of the present invention may include other layers (or films) besides those described above. Examples of other layers include, for instance, an adhesive layer laminated on the outer surfaces of the first thermoplastic resin film 10, the second thermoplastic resin film 20, and / or the polarizer 30; a release film (also called a "release film") laminated on the outer surface of the adhesive layer; a protective film (also called a "surface protection film") laminated on the outer surfaces of the first thermoplastic resin film 10, the second thermoplastic resin film 20, and / or the polarizer 30; and an optically functional film (or layer) laminated on the outer surfaces of the first thermoplastic resin film 10, the second thermoplastic resin film 20, and / or the polarizer 30 via an adhesive layer and an adhesive layer.
[0137] [2] Polarizing plate
[0138] Polarizer 30 is a film that selectively transmits linearly polarized light in a certain direction from natural light. Examples of polarizers 30 include iodine-based polarizers obtained by adsorbing and oriented iodine as a dichroic pigment onto a polyvinyl alcohol-based resin film; dye-based polarizers obtained by adsorbing and oriented dichroic dyes as dichroic pigments onto a polyvinyl alcohol-based resin film; and coated polarizers obtained by coating a dichroic dye in a lyotropic liquid crystal state, oriented it, and immobilizing it. These polarizers are called absorption-type polarizers because they selectively transmit linearly polarized light in one direction from natural light and absorb linearly polarized light in another direction.
[0139] The polarizer 30 is not limited to an absorptive polarizer. It can also be a reflective polarizer that selectively transmits linearly polarized light in one direction from natural light, reflects linearly polarized light in another direction, or scatters linearly polarized light in another direction. However, from the perspective of excellent visibility when the polarizer is applied to an image display device, etc., an absorptive polarizer is preferred.
[0140] The polarizer 30 is more preferably a polyvinyl alcohol polarizer made of polyvinyl alcohol resin, and even more preferably a polyvinyl alcohol polarizer obtained by adsorbing iodine, dichroic dyes and other dichroic pigments on a polyvinyl alcohol resin film and orienting them. It is particularly preferably a polyvinyl alcohol polarizer (polyvinyl alcohol-iodine polarizer) obtained by adsorbing iodine on a polyvinyl alcohol resin film and orienting it.
[0141] Polyvinyl alcohol polarizers can be manufactured using polyvinyl alcohol resin films (or layers) using conventionally known methods.
[0142] The thickness of the polarizer 30 can be set to 30 μm or less, preferably 25 μm or less (for example, it can be 20 μm or less, further preferably 15 μm or less, even further preferably 10 μm or less, and even further preferably 8 μm or less). The thickness of the polarizer 30 is typically 2 μm or more. Reducing the thickness of the polarizer 30 is beneficial for making the polarizer thinner, and thus beneficial for making image display devices and the like that using the polarizer thinner.
[0143] [3] Second thermoplastic resin film
[0144] The second thermoplastic resin film 20 can be a film containing a light-transmitting (preferably optically transparent) thermoplastic resin, such as a film containing polyolefin resins such as chain polyolefin resins (polyethylene resins, polypropylene resins, etc.), cyclic polyolefin resins such as norbornene resins, cellulose ester resins such as triacetyl cellulose and diacetyl cellulose, polyester resins such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polycarbonate resins, and (meth)acrylic resins.
[0145] The second thermoplastic resin film 20 can be the optical film of the present invention.
[0146] When the second thermoplastic resin film 20 is a (meth)acrylic resin film, the resin composition constituting the second thermoplastic resin film 20 may differ from the resin composition constituting the optical film of the present invention in terms of composition, etc.
[0147] The second thermoplastic resin film 20 can be either an unstretched film or a film that has undergone uniaxial or biaxial stretching. Biaxial stretching can be simultaneous biaxial stretching along two stretching directions, or it can be successive biaxial stretching, where the film is stretched along a first direction and then stretched along a second direction that is different from it.
[0148] The second thermoplastic resin film 20 can be a protective film that serves to protect the polarizer 30, or it can be a protective film with optical functions, such as a phase retardation film. For example, a phase retardation film with arbitrary phase difference values can be made by stretching the film containing the thermoplastic resin (uniaxial stretching or biaxial stretching, etc.) or forming a liquid crystal layer on the thermoplastic resin film.
[0149] The second thermoplastic resin film 20 may contain additives as needed. Examples of additives include lubricants, anti-blocking agents, heat stabilizers, antioxidants, UV absorbers, antistatic agents, impact modifiers, surfactants, and release agents.
[0150] In one embodiment, the first thermoplastic resin film 10 is the optical film of the present invention, and the second thermoplastic resin film 20 is a polyolefin resin film (preferably a cyclic polyolefin resin film), a cellulose ester resin, or a polyester resin film.
[0151] In another embodiment, the first thermoplastic resin film 10 is the optical film of the present invention, and the second thermoplastic resin film 20 is a (meth)acrylic resin film. The (meth)acrylic resin film can be the optical film of the present invention.
[0152] The second thermoplastic resin film 20 may have coatings (surface treatment layers) such as a hard coating layer, an anti-glare layer, an anti-reflection layer, a light diffusion layer, an antistatic layer, an anti-fouling layer, and a conductive layer on its outer surface (the surface opposite to the polarizer 30).
[0153] The thickness of the second thermoplastic resin film 20 is typically 5 μm or more and 200 μm or less, preferably 10 μm or more and 120 μm or less, more preferably 10 μm or more and 85 μm or less, and even more preferably 15 μm or more and 65 μm or less. The thickness of the second thermoplastic resin film 20 may also be 60 μm or less, or 50 μm or less. Reducing the thickness of the second thermoplastic resin film 20 facilitates the thinning of the polarizing plate, and consequently facilitates the thinning of image display devices and the like that utilize this polarizing plate.
[0154] [4] Manufacturing of polarizing plate and adhesive layer
[0155] By laminating and bonding the first thermoplastic resin film 10, which serves as the optical film of the present invention, to one side of the polarizer 30 via the first adhesive layer 15, a result can be obtained. Figure 1 The polarizing plate shown can be obtained by further laminating and bonding a second thermoplastic resin film 20 to the other side of the polarizing plate 30 via a second adhesive layer 25. Figure 2 The polarizing plate shown is configured as follows.
[0156] In manufacturing a polarizing plate having both a first thermoplastic resin film 10 and a second thermoplastic resin film 20 (hereinafter also simply referred to collectively as "thermoplastic resin films"), these thermoplastic resin films can be laminated and bonded one side at a time in stages, or the thermoplastic resin films on both sides can be laminated and bonded simultaneously.
[0157] Examples of adhesive compositions forming the first adhesive layer 15 and the second adhesive layer 25 include water-based adhesives and active energy radiation-curable adhesives. The adhesive composition forming the first adhesive layer 15 may be the same as or different from the adhesive composition forming the second adhesive layer 25.
[0158] The adhesive used in bonding the optical film and the polarizer of the present invention is preferably an active energy radiation-curable adhesive.
[0159] Examples of water-based adhesives include conventionally known adhesive compositions using polyvinyl alcohol resins or urethane resins as the main component. Reactive energy radiation-curable adhesives are adhesives that cure by irradiation with reactive energy radiation such as ultraviolet light, visible light, electron beams, or X-rays. In the case of using a reactive energy radiation-curable adhesive, the adhesive layer of the polarizing plate is a cured layer of that adhesive.
[0160] The active energy radiation-curable adhesive can be an adhesive containing an epoxy compound that is cured by cationic polymerization as a curing component, and preferably an ultraviolet-curable adhesive containing such an epoxy compound as a curing component. An epoxy compound is defined as a compound having an average of one or more, preferably two or more, epoxy groups within its molecule. Only one epoxy compound may be used, or two or more may be used in combination.
[0161] Examples of epoxy compounds include hydrogenated epoxy compounds (glycidyl ethers of polyols having an alicyclic ring) obtained by reacting epichlorohydrin with an aromatic ring of an aromatic polyol; aliphatic epoxy compounds such as polyglycidyl ethers of aliphatic polyols or their epoxide alkane adducts; and alicyclic epoxy compounds having one or more epoxy groups bonded to an alicyclic ring within the molecule.
[0162] Active energy radiation-curable adhesives can replace the aforementioned epoxy compounds, or (meth)acrylic acid compounds containing free radical polymerizability, as curing agents. Examples of (meth)acrylic acid compounds include (meth)acrylic acid ester monomers having one or more (meth)acryloyloxy groups within the molecule; (meth)acrylic acid ester oligomers having at least two (meth)acryloyloxy groups within the molecule, obtained by reacting two or more compounds containing functional groups.
[0163] In the case where the active energy ray-curable adhesive contains an epoxy compound that is cured by cationic polymerization as a curing component, it is preferable to contain a photocationic polymerization initiator. Examples of photocationic polymerization initiators include aromatic diazonium salts; aromatic iodonium salts, aromatic sulfonium salts, and other sulfonium salts; iron-aromatic complexes, etc.
[0164] When an active energy radiation-curable adhesive contains free radical polymerizable components such as (meth)acrylic acid compounds, it is preferable to include a photoradical polymerization initiator. Examples of photoradical polymerization initiators include acetophenone-based initiators, benzophenone-based initiators, benzoin ether-based initiators, thioxanthone-based initiators, xanthones, fluorenones, camphorquinone, benzaldehyde, and anthraquinones.
[0165] The bonding of the polarizer 30 to the thermoplastic resin film may include the following steps: applying an adhesive composition to the bonding surface of the polarizer 30 and / or the bonding surface of the thermoplastic resin film, or injecting an adhesive composition between the polarizer 30 and the thermoplastic resin film, and overlapping the two films through the layers of adhesive composition, for example, by pressing from above and below using a bonding roller.
[0166] The adhesive composition layer can be formed using various coating methods, such as a scraper, a wire-winding bar, a die-coating machine, a comma-type coating machine, or a gravure coating machine. Alternatively, the adhesive composition can be cast between the polarizing film 30 and the thermoplastic resin film, with their bonding surfaces facing inwards.
[0167] Before applying the adhesive composition, one or both of the bonding surfaces of the polarizer 30 and the thermoplastic resin film can be subjected to easy-bonding treatments (surface activation treatments) such as saponification, corona discharge, plasma treatment, flame treatment, primer treatment, and anchor coating treatment.
[0168] In the case of using an active energy ray curable adhesive, the adhesive composition layer is cured by irradiating it with active energy rays.
[0169] The light source used for irradiating active energy rays can be any light source capable of producing ultraviolet rays, electron beams, X-rays, etc. In particular, light sources with luminous distribution at wavelengths below 400nm, such as low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps, can be used appropriately.
[0170] The thicknesses of the first adhesive layer 15 and the second adhesive layer 25 in the polarizing plate are, for example, 0.1 μm or more and 100 μm or less, preferably 0.5 μm or more and 80 μm or less, more preferably 1 μm or more and 60 μm or less, and even more preferably 2 μm or more and 50 μm or less. From the viewpoint of making the polarizing plate thinner, it is also preferable to set the thickness of the adhesive layer to 30 μm or less, more preferably 20 μm or less. When using a water-based adhesive, the thickness of the adhesive layer can be even smaller than the above-mentioned thicknesses.
[0171] The thicknesses of the first adhesive layer 15 and the second adhesive layer 25 can be the same or different.
[0172] [5] Other constituent elements of the polarizing plate
[0173] [5-1] Optical functional films
[0174] The polarizer may have other optically functional films besides the polarizer 30 to impart the desired optical function, a suitable example being a phase retardation film.
[0175] As described above, the second thermoplastic resin film 20 can also serve as a retardation film; however, a retardation film can also be laminated separately outside the thermoplastic resin film. In the latter case, the retardation film can be laminated onto the outer surface of the second thermoplastic resin film 20 via an adhesive layer and a bonding agent layer. Alternatively, the retardation film can be laminated instead of the second thermoplastic resin film 20. For example, a specific example would be... Figure 1 The configuration shown below is such that, in a single-sided protective polarizing plate in which a first thermoplastic resin film 10 is attached to one side of the polarizer 30, a phase retardation film is attached to the other side of the polarizer 30. In this case, the phase retardation film can be laminated onto the surface of the polarizer 30 via an adhesive layer or a bonding agent layer.
[0176] Examples of phase retardation films include birefringent films made of stretched films of thermoplastic resins with light transmittance; films formed by oriented and fixed disc-shaped liquid crystals or nematic liquid crystals; and films on which the above-mentioned liquid crystal layers are formed on a substrate film.
[0177] The substrate film is usually a film containing a thermoplastic resin, an example of which is a cellulose ester resin such as triacetyl cellulose.
[0178] As the thermoplastic resin for forming the birefringent film, the resin described for the second thermoplastic resin film 20 can be used.
[0179] Examples of other optical functional films (optical components) that can be included in a polarizing plate include a light-concentrating plate, a brightness enhancement film, a reflective layer, a semi-transparent reflective layer, and a light-diffusing layer. These are generally provided when the polarizing plate is a polarizing plate disposed on the back side (backlight side) of the liquid crystal cell.
[0180] [5-2] Adhesive layer
[0181] The polarizing plate of the present invention may include an adhesive layer for bonding it to image display elements such as liquid crystal cells, organic EL elements, or other optical components. The adhesive layer is... Figure 1 The polarizing plate shown can be stacked on the outer surface of the polarizer 30 (the side opposite to the side of the first thermoplastic resin film 10), in Figure 2 The polarizing plate shown can be laminated on the outer surface of the first thermoplastic resin film 10 or the second thermoplastic resin film 20.
[0182] In a preferred embodiment of the polarizer, an adhesive layer is laminated on the outer surface of the second thermoplastic resin film 20, that is, the side opposite to the side of the first thermoplastic resin film 10 with reference to the polarizer 30. In this embodiment, when the polarizer is attached to the image display element, the polarizer is attached to the image display element via the adhesive layer such that the side of the first thermoplastic resin film 10 is the viewing side.
[0183] As an adhesive used in the adhesive layer, adhesives with (meth)acrylic resins, silicone resins, polyester resins, polyurethane resins, polyether resins, etc., as base polymers can be used. Among them, (meth)acrylic adhesives are preferred from the viewpoints of transparency, adhesion, reliability, weather resistance, heat resistance, and reprocessability.
[0184] The thickness of the adhesive layer is determined based on its adhesive strength, etc., and is suitable in the range of 1 μm or more and 50 μm or less, preferably 2 μm or more and 40 μm or less.
[0185] The polarizing plate may include a release film laminated on the outer surface of the adhesive layer. The release film may be a film containing polyethylene resins such as polyethylene, polypropylene resins such as polypropylene, polyester resins such as polyethylene terephthalate, etc. Among them, a stretch film of polyethylene terephthalate is preferred.
[0186] The adhesive layer may include, as needed, glass fibers, glass beads, resin beads, fillers formed from metal powder or other inorganic powders, pigments, colorants, antioxidants, ultraviolet absorbers, antistatic agents, etc.
[0187] [5-3] Protective film
[0188] The polarizing plate of the present invention may include a protective film for protecting its surface (the surface of the thermoplastic resin film, the surface of the polarizer, etc.). After the polarizing plate is bonded to, for example, an image display element or other optical component, the protective film, together with its adhesive layer, is peeled off.
[0189] In a preferred embodiment, a polarizing plate is laminated on the surface of a first thermoplastic resin film 10, which serves as the optical film of the present invention.
[0190] The protective film, for example, consists of a substrate film and an adhesive layer laminated thereon. The above description can be cited regarding the adhesive layer.
[0191] The resin constituting the substrate film can be, for example, a polyethylene-based resin such as polyethylene, a polypropylene-based resin such as polypropylene, a polyester-based resin such as polyethylene terephthalate or polyethylene naphthalate, or a thermoplastic resin such as polycarbonate. Polyester-based resins such as polyethylene terephthalate are preferred.
[0192] Example
[0193] The present invention will be further described in detail below with reference to examples; however, the present invention is not limited to these examples. In the examples, the percentages and parts representing the content or amount used are quality standards unless otherwise specified. The thickness of the film and adhesive layer (cured layer) was measured using a digital micrometer “MH-15M” manufactured by Nikon Corporation.
[0194] <Example 1>
[0195] (1) Fabrication of optical film I
[0196] Prepare the following raw materials.
[0197] • (Meth)acrylic resin (A): A methacrylic resin (homogeneous polymer of methyl methacrylate) with a syndiotactic normality (rr) of 76% as represented by a ternary group.
[0198] • (Meth)acrylic resin (B-1): A free radical copolymer with a syndiotactic normality (rr) of 48%, represented by a terunit group of methyl methacrylate / methyl acrylate = 97 / 3 (mass ratio).
[0199] • Elastomer component (C): (Meth)acrylic rubber particles comprising a three-layer (meth)acrylic multilayer polymer (first layer (innermost layer): copolymer of methyl methacrylate and methyl acrylate and allyl methacrylate (mass ratio 93.8 / 6.0 / 0.2) / second layer: copolymer of butyl acrylate and styrene and allyl methacrylate (mass ratio 80.6 / 17.4 / 2.0) / third layer (outermost layer): copolymer of methyl acrylate and ethyl acrylate (mass ratio 94 / 6))
[0200] An unstretched resin film (resin layer) with a thickness of 50 μm was produced by melt extrusion of a mixture of 20 parts of (meth)acrylic resin (A), 55 parts of (meth)acrylic resin (B-1), and 25 parts of elastomer component (C).
[0201] The following components were dissolved in propylene glycol monomethyl ether to obtain a UV-curable resin composition. The resin solids content in the UV-curable resin composition was 50%.
[0202] 60 parts of pentaerythritol triacrylate
[0203] 40 parts of polyfunctional carbamate acrylate (reaction product of hexamethylene diisocyanate and pentaerythritol triacrylate)
[0204] For the above-mentioned UV-curable resin composition, 2.5 parts by weight of "Omnirad 184" (manufactured by IGM Resins BV) and 1 part by weight of "Omnirad 819" (manufactured by IGM Resins BV) were added as photoradical polymerization initiators per 100 parts of the resin solids content. After mixing, the mixture was applied to one side of the resin film using a bar coater and dried at 80°C for 3 minutes. The dried coating was then tested using a Fusion H-lamp as the light source, with a cumulative light intensity of 200 mJ / cm². 2 An optical film I with a hard coating was created by irradiating the surface of a resin layer with ultraviolet light. The thickness of the hard coating single film was 5 μm.
[0205] (2) Fabrication of polarizing plates
[0206] The surface of optical film I (the surface opposite to the hard coating) is subjected to corona treatment, and a curable adhesive composition A is applied to the corona-treated surface using an adhesive coating apparatus. The resulting coating layer and a 23 μm thick polyvinyl alcohol-iodine polarizer are then laminated using clamping rollers to obtain a polarizer with optical film I. In the polarizer with optical film I, the mechanical flow direction (MD direction) of optical film I is parallel to the absorption axis of the polarizer.
[0207] Next, a 50 μm thick retardation film (trade name "ZEONOR" manufactured by ZEON Corporation of Japan) containing a cyclic polyolefin resin was subjected to corona treatment. A curable adhesive composition B was then applied to the corona-treated surface using an adhesive coating apparatus. The resulting coated layer and the polarizer surface of a polarizer containing optical film I were then laminated using clamping rollers to obtain a laminate. In this laminate, the mechanical flow direction (MD direction) of the retardation film is parallel to the absorption axis of the polarizer.
[0208] The total cumulative light intensity (cumulative light intensity in the wavelength region of 320–400 nm) irradiated from the phase retardation film side of this laminate is approximately 200 mJ / cm². 2 (Measurement values obtained using a UV Power Puck II measuring instrument manufactured by FusionUV Corporation) Ultraviolet light (UVB) is used to cure layers of both the curable adhesive composition B and the curable adhesive composition A, thereby producing a polarizing plate. It should be noted that the thickness of the cured layer of both the curable adhesive composition A and the cured layer of both the curable adhesive composition B is approximately 3 μm.
[0209] The curable adhesive composition A is prepared as follows: 20 parts of 3,4-epoxycyclohexanecarboxylic acid 3',4'-epoxycyclohexylmethyl ester (trade name "Celloxide 2021P" manufactured by Daicel Co., Ltd.), 70 parts of neopentyl glycol diglycidyl ether (trade name "EX-211L" manufactured by Nagase ChemteX Co., Ltd.), 2 parts of 4-hydroxybutylvinyl ether (trade name "HBVE" manufactured by Carbide Japan), 8 parts of methyl methacrylate-glycidyl methacrylate copolymer (cationic polymer) (trade name "Marproof G-01100" manufactured by Nippon Oil Co., Ltd.), and 2.25 parts of the solid component of photopolymerization initiator (trade name "CPI-100P" manufactured by San-Apro Co., Ltd.) are mixed and degassed.
[0210] The curable adhesive composition B is prepared as follows: 100 parts of 3',4'-epoxycyclohexyl methyl ester (trade name "Celloxide2021P" manufactured by Daicel Co., Ltd.), 25 parts of 1,4-butanediol diglycidyl ether (trade name "EX-214L" manufactured by Nagase ChemteX Co., Ltd.), and 2.8 parts of the solid component of a photopolymerization initiator (trade name "CPI-100P" manufactured by San-Apro Co., Ltd.) are mixed and degassed.
[0211] <Example 2>
[0212] (1) Fabrication of optical film II
[0213] An unstretched resin film (resin layer) with a thickness of 50 μm was produced by melt extrusion from a mixture of 21 parts of (meth)acrylic resin (A), 59 parts of (meth)acrylic resin (B-1), and 20 parts of elastomer component (C). The same substances as in Example 1 were used for (meth)acrylic resin (A), (meth)acrylic resin (B-1), and elastomer component (C). In addition to using this resin film, a hard coating was formed in the same manner as in Example 1 to produce optical film II.
[0214] (2) Fabrication of polarizing plates
[0215] The polarizing plate was fabricated in the same manner as in Example 1, except that optical film II was used instead of optical film I.
[0216] <Comparative Example 1>
[0217] (1) Fabrication of optical film III
[0218] An unstretched resin film (resin layer) with a thickness of 50 μm was produced by melt extrusion of a mixture of 75 parts of (meth)acrylic resin (A) and 25 parts of elastomer component (C). The same substances as in Example 1 were used for (meth)acrylic resin (A) and elastomer component (C). In addition to using this resin film, a hard coating was formed in the same manner as in Example 1 to produce optical film III.
[0219] (2) Fabrication of polarizing plates
[0220] The polarizing plate was fabricated in the same manner as in Example 1, except that optical film III was used instead of optical film I.
[0221] <Example 3>
[0222] (1) Fabrication of optical film IV
[0223] Prepare the following raw materials.
[0224] • (Meth)acrylic resin (B-2): A free radical copolymer with a syndiotactic normality (rr) of 51%, represented by a terunit group of methyl methacrylate / methyl acrylate ratio of 98.6 / 1.4 (mass ratio).
[0225] An unstretched resin film (resin layer) with a thickness of 60 μm was produced by melt extrusion from a mixture of 12 parts of (meth)acrylic resin (A), 68 parts of (meth)acrylic resin (B-2), and 20 parts of elastomer component (C). The same substances as in Example 1 were used for (meth)acrylic resin (A) and elastomer component (C). In addition to using this resin film, a hard coating was formed in the same manner as in Example 1 to produce optical film IV.
[0226] (2) Fabrication of polarizing plates
[0227] The polarizing plate was fabricated in the same manner as in Example 1, except that optical film IV was used instead of optical film I.
[0228] <Example 4>
[0229] (1) Fabrication of optical film V
[0230] An unstretched resin film (resin layer) with a thickness of 60 μm was produced by melt extrusion from a mixture of 7.5 parts of (meth)acrylic resin (A), 67.5 parts of (meth)acrylic resin (B-2), and 25 parts of elastomer component (C). The same substances as in Example 1 were used for (meth)acrylic resin (A) and elastomer component (C). In addition to using this resin film, a hard coating was formed in the same manner as in Example 1 to produce an optical film V.
[0231] (2) Fabrication of polarizing plates
[0232] The polarizing plate was fabricated in the same manner as in Example 1, except that optical film V was used instead of optical film I.
[0233] <Example 5>
[0234] (1) Fabrication of optical film VI
[0235] An unstretched resin film (resin layer) with a thickness of 60 μm was produced by melt extrusion from a mixture of 22.5 parts of (meth)acrylic resin (A), 52.5 parts of (meth)acrylic resin (B-2), and 25 parts of elastomer component (C). The same substances as in Example 1 were used for (meth)acrylic resin (A) and elastomer component (C). In addition to using this resin film, a hard coating was formed in the same manner as in Example 1 to produce optical film VI.
[0236] (2) Fabrication of polarizing plates
[0237] The polarizing plate was fabricated in the same manner as in Example 1, except that optical film VI was used instead of optical film I.
[0238] <Example 6>
[0239] (1) Fabrication of optical film VII
[0240] An unstretched resin film (resin layer) with a thickness of 60 μm was produced by melt extrusion from a mixture of 14 parts of (meth)acrylic resin (A), 56 parts of (meth)acrylic resin (B-2), and 30 parts of elastomer component (C). The same substances as in Example 1 were used for (meth)acrylic resin (A) and elastomer component (C). In addition to using this resin film, a hard coating was formed in the same manner as in Example 1 to produce optical film VII.
[0241] (2) Fabrication of polarizing plates
[0242] The polarizing plate was fabricated in the same manner as in Example 1, except that optical film VII was used instead of optical film I.
[0243] <Measurement and Evaluation>
[0244] (1) Determination of the tensile elastic modulus of optical films
[0245] (1-1) Determination of tensile modulus of elasticity in the MD direction at 23℃
[0246] A rectangular test piece with a length of 100 mm and a width of 10 mm was cut from the optical film obtained above. The length direction of the test piece was parallel to the MD direction of the optical film and parallel to the absorption axis of the polarizer of the fabricated polarizing plate. The width direction of the test piece was parallel to the TD direction of the optical film (the direction orthogonal to the MD direction) and orthogonal to the absorption axis of the polarizer of the fabricated polarizing plate. Then, the test piece was clamped at both ends along the length direction (MD direction of the optical film) with the upper and lower clamps of a tensile testing machine (Autograph AG-1S testing machine manufactured by Shimadzu Corporation) with the clamps spaced 5 cm apart. At 23°C, the test piece was stretched along the length direction (MD direction of the optical film) at a tensile speed of 50 mm / min. The elastic modulus (tensile elastic modulus) [MPa] of the optical film in the MD direction at 23°C was calculated based on the slope of the initial straight line of the obtained stress-strain curve.
[0247] (1-2) Determination of tensile modulus of elasticity in the TD direction at 23℃
[0248] A rectangular test piece with a length of 100 mm and a width of 10 mm was cut from the optical film obtained above. The length direction of the test piece is parallel to the TD direction of the optical film and orthogonal to the absorption axis of the polarizer of the fabricated polarizing plate. The width direction of the test piece is parallel to the MD direction of the optical film and parallel to the absorption axis of the polarizer of the fabricated polarizing plate. Then, the test piece is clamped at both ends along the length direction (TD direction of the optical film) with the upper and lower clamps of a tensile testing machine (Autograph AG-1S testing machine manufactured by Shimadzu Corporation) with the clamps spaced 5 cm apart. At 23°C, the test piece is stretched along the length direction (TD direction of the optical film) at a tensile speed of 50 mm / min. The elastic modulus (tensile elastic modulus) [MPa] of the optical film in the TD direction at 23°C is calculated based on the slope of the initial straight line of the obtained stress-strain curve.
[0249] (1-3) Determination of tensile modulus of elasticity at 80℃
[0250] In addition to measuring at 80°C, the tensile modulus of elasticity in the MD direction and the tensile modulus of elasticity in the TD direction at 80°C were measured in the same manner as in (1-1) and (1-2) above.
[0251] The tensile modulus of elasticity in the MD direction at each temperature is represented in the "MD" column of Table 1, and the tensile modulus of elasticity in the TD direction is represented in the "TD" column of Table 1. In addition, the tensile modulus of elasticity in the TD direction is divided by the tensile modulus of elasticity in the MD direction, and the resulting value is represented in the "TD / MD" column of Table 1.
[0252] (2) Determination of Charpy impact strength of optical film
[0253] A rectangular test piece with a length of 100 mm and a width of 10 mm was cut from the optical film obtained above. Using the obtained test piece, a Charpy impact test was conducted according to ISO 179-1 and JIS K7111-1, using a 1J pendulum (rotational torque: 0.540116 N·m), at an environment of 23℃ and 50% RH. The absorbed energy (kJ / m²) was... 2 Ten measurements were performed, and the average value was used. The results are shown in Table 1.
[0254] (3) Determination of pencil hardness of optical film
[0255] According to JIS K5600-5-4, the scratch hardness was measured using a Yasuda Seiki Co., Ltd. No. 553-M1 electric pencil scratch hardness tester. First, the optical film was fixed to a glass plate with the hard coating facing upwards using tape. A pencil was placed at a 45-degree angle, a load of 500g was applied, and the sample surface (hard coating surface) was scratched. Five tests were performed using pencils of the same hardness. The same scratch test was then performed with pencils of varying hardness from F to 2H. The scratched film was placed on a blackboard, and the presence or absence of scratches on the film surface was observed using fluorescent light. The highest pencil hardness, where no scratches were produced in four or more of the five tests, was taken as the pencil hardness of the film. The results are shown in Table 1.
[0256] (4) Evaluation of fit
[0257] (4-1) Initial tightness
[0258] An adhesive layer is formed on the optical film side (the side opposite to the retardation film) of the obtained polarizer. The obtained polarizer with the adhesive layer is cut into pieces with a length (parallel to the absorption axis of the polarizer) of 200 mm × a width of 25 mm, and the adhesive layer is bonded to a glass plate to obtain a laminate. It is placed in an environment with a temperature of 23°C and a relative humidity of 50% RH for 24 hours. Then, a cutting blade is inserted between the polarizer and the optical film of the obtained laminate, and 30 mm is peeled off from the end along the length direction. The peeled part is held by the clamping part of the testing machine, with the glass plate held by the lower part of the clamp. For the test piece in this condition, a peel test was conducted in an atmosphere of 23°C and 55% relative humidity, according to JIS K6854-2:1999 "Adhesives - Peel strength test method - Part 2: 180-degree peel", with a clamp moving speed of 300 mm / min. The average peel force (unit: N / 25 mm) over a length of 60 mm excluding the clamp portion was calculated and taken as the peel strength between the polarizer and the optical film. The results are shown in Table 1.
[0259] (4-2) Adhesion after exposure to high temperature and high humidity environment
[0260] An adhesive layer is formed on the optical film side (the side opposite to the retardation film) of the obtained polarizer. The obtained polarizer with the adhesive layer is cut into pieces with a length (parallel to the absorption axis of the polarizer) of 200 mm × a width of 25 mm, and the adhesive layer is bonded to a glass plate to obtain a laminate. The obtained laminate is placed in a high temperature and high humidity environment of 80°C and 90% RH for 24 hours, and then placed in an environment of 23°C and 50% RH for 24 hours. Subsequently, a cutting blade is inserted between the polarizer and the optical film of the obtained laminate, and 30 mm is peeled off from the end along the length direction. The peeled part is held by the clamping part of the testing machine, and the glass plate is held by the lower part of the clamp. For the test piece in this condition, a peel test was conducted in an atmosphere with a temperature of 23°C and a relative humidity of 55%, according to JIS K 6854-2:1999 "Adhesives - Peel strength test method - Part 2: 180-degree peel", with a clamp moving speed of 300 mm / min. The average peel force (unit: N / 25 mm) over a length of 60 mm excluding the clamp portion was calculated and taken as the peel strength between the polarizer and the optical film. The results are shown in Table 1.
[0261] [Table 1]
[0262]
[0263] Explanation of reference numerals in the attached figures
[0264] 10 First thermoplastic resin film, 15 First adhesive layer, 20 Second thermoplastic resin film, 25 Second adhesive layer, 30 Polarizing film.
Claims
1. A polarizing plate, comprising, in sequence, a polarizer, an adhesive layer, and an optical film, wherein, The optical film comprises a resin layer containing (meth)acrylic resin A, (meth)acrylic resin B, and elastomer component C. The isotacticity of (meth)acrylic resin A is higher than that of (meth)acrylic resin B. When the content of the (meth)acrylic resin A in the resin layer is set as A, and the content of the elastomer component C is set as C, the resin layer satisfies the following formula [1]: 0.2 The units for A and C mentioned above are parts by mass; 2. The polarizing plate according to claim 1, wherein, At an environment of 23°C and 50% RH, the absorbed energy of the resin layer, as determined by the Charpy impact test, is 140 kJ / m. 2 Above, and 350kJ / m 2 the following. When the content of the (meth)acrylic resin B in the resin layer is set to B, the following formula [2] is further satisfied: 0.05≤A / (A+B)≤0.4 Equation [2] The unit of B is parts by mass.
3. The polarizing plate according to claim 1 or 2, wherein, The elastomer component C is rubber particles. The optical film also includes a surface treatment layer laminated on the resin layer.
4. The polarizing plate according to claim 1 or 2, wherein, The optical film is a protective film for polarizers.
5. The polarizing plate according to claim 1 or 2, wherein,
Citation Information
Patent Citations
Polarizer, polarization plate, optical film and image display apparatus
JP2008102274A
Set of polarizing plates and liquid crystal panel and liquid crystal display device using the same
JP2009145397A
Methacrylic resin composition, molded body, and method for producing methacrylic resin composition
JP2021155698A
Methacrylate resin composition, method for producing same, molded body, film, laminated film, and laminated molded body
CN109563328A